Solvation and diffusion of poly(vinyl alcohol) chains in a hydrated inorganic ionic liquid. Issue 31 (30th July 2020) - Karimineghlani, Parvin; Zheng, Jin; Hu, Yan-Yan; Sukhishvili, Svetlana
Abstract : Studies of the behavior of poly(vinyl alcohol) in a hydrated inorganic ionic liquid revealed good solvent conditions for polymer chains. Abstract : While the behavior of polyelectrolyte chains in aqueous salt solutions has been extensively studied, little is known about polar polymer chains in solvents with extremely high concentrations of inorganic ions, such as those found in ionic liquids (ILs). Here, we report on expansion, solvation and diffusion of poly(vinyl alcohol), PVA, chains in dilute solutions of a hydrated inorganic IL phase change material (PCM), lithium nitrate trihydrate (LNH). This solvent has an extremely high concentration of inorganic ions (≈18 M) with a low concentration of water molecules largely forming solvation shells of Li + and NO3 − ions, as shown using ATR-FTIR spectroscopy. Diffusion and hydrodynamic size of PVA chains of different molecular weights in this unusual solvent were studied using fluorescence correlation spectroscopy (FCS). A higher scaling exponent obtained from the molecular weight dependences of the diffusion coefficients of PVA chains as well as a lower overlap concentration ( c *) of PVA in LNH solutions as measured by FCS suggest an expansion of the polymer coils in this solvent. We argue that enhanced solubility of PVA in LNH solutions is likely a result of increased rigidification of polymer chains due to the binding of solvated Li + ions, which is demonstrated using 7 Li NMR spectroscopy. We believe that an understanding of solvation and ion-binding capability can offer crucial insight into designing polymer-based shape stabilization matrices for inorganic PCMs.